Effect of heating energy, steel fibres, bitumen types and ageing on the self-healing phenomena in hot mix asphalt - Ajam, Harith K.K. (2019)
Hot mix asphalt is one of the most common types of pavement surface materials used in the world. The combined effects of traffic loading and the environment will cause every flexible pavement, no matter how well-designed/constructed to deteriorate over time. Once a crack is open in the pavement, and because of bitumen viscoelastic properties, it starts healing and, if it has enough rest time, it can even close completely. Furthermore, asphalt self-healing is a viscosity related phenomenon that accelerates by reducing the viscosity of bitumen as it increases the capillarity flow through the cracks. One method to achieve this is by exposing the pavement to heat energy, which also produces a thermal expansion that contributes to the circulation of the bitumen through cracks. In this research, three aspects were investigated. Firstly, asphalt self-healing has been induced in cracked asphalt beams with different air voids contents (dense, semi-dense and porous) by exposing them for various times under infrared radiation and induction heating. Infrared heating has been used to simulate solar radiation. The results show that both methods reach similar and satisfactory healing ratios at around 90%. However, induction heating is more energy efficient because the effect is concentrated on the binder, instead of heating the whole mix. This can be translated into much shorter heating times to reach the same healing level. An optimum healing energy was found, after which higher amounts of infrared radiation damage the properties of the healed material. Moreover, it has been observed that dense mixtures obtained better healing with low energy but the maximum healing ratios obtained by them were lower than those obtained by semi-dense and porous mixtures by about 12 to 15% respectively. A new healing model was proposed involving not only surface tension, hydrostatic forces and energy dissipation but also other factors, such as differential temperature between aggregates and binder and thermal expansion. Secondly, improper disposal of metal waste in landfills is one of the primary means by which metals, mainly produced in different industrial sectors, reach the soil and ground water. These can migrate to surrounding ecosystems and bio-magnify in plants and animals endangering the human food chain. At the same time, the addition of metal particles in asphalt mixes produces a series of beneficial effects, such as enhancing their mechanical performance, durability and electrical conductivity making possible applications, such as ice/snow melting and crack healing by electromagnetic induction. Research was undertaken to assess and compare the use of two different types of waste metal fibres (recovered from old tyres and shavings from the machining industry) and two other types of commercial particles (steel wool and steel grit) regarding their effect on volumetric, mechanical and healing properties of asphalt mixes. General results showed that all fibres improve the mix properties with similar healing, mechanical and leaching properties, and with a proper design, the improvement in such properties by using waste metals is comparable to that obtained by using commercial particles. It was also found that fibres from old tyres are especially suitable for low structural layers (base and sub-base), while the use of metal shavings is particularly recommended in superficial courses. Finally, the effect of bitumen was studied in two forms: aged and virgin. Over the service life of asphalt roads, different factors produce, in the bitumen, a hardening process known as “ageing”. Also, the addition of recycled, aged material (i.e. RAP) to new mixes modifies the viscosity of the mix. The research studied how these two actions affect the capacity for healing, by electromagnetic induction, of asphalt mixes. Mixes subjected to different ageing processes or containing different amounts of RAP were tested. Results show that both ageing and RAP content contribute to increasing binder stiffness and air voids content in the mix. Therefore, the healing process becomes less effective and energy efficient. For the worst ageing and RAP stage, still more than 20% healing occurred. On the other hand, the influence of virgin bitumen properties on the induction healing capacity of asphalt mixtures was studied. The main conclusion that can be extracted is that, for the range of bitumens commonly used, the fact of changing the type of bitumen does not significantly affect the healing capacity of the resulting asphalt mix.